Enhanced Control of a Photovoltaic Water Pumping System by DTC-SVM - Hocine Ihab, AZZA; Ahmed, MESAI BELGACEM (University Of El Oued, 2020)
This thesis proposes an improved provide a (DTC) technique to control the used motor in the photovoltaic system. The main contribution of this work ensures an optimum power operation (MPPT) of this system for different climate conditions, the (P&O) algorithm is used to generate the appropriate reference for direct torque control technique with space vector modulation (DTC-SVM). This is achieved by the stand-alone solar water pumping system is one of the proposed solutions for them, and it needs less intervention than other renewable energy systems by applying a system consists of a photovoltaic generator, which is connected to a voltage source inverter supplying an induction motor coupled to a centrifugal pump. To validate the whole system's performance, we presented and discussed the result using the MATLAB/SIMULINK software environment. The solar water pumping system is stable and gave satisfactory results, the DTC - SVM control is reduced the torque and flux ripples, with a fewer harmonics of induction motor current, where the electromagnetic torque of the induction motor tracked the load torque that was produced by the pump and controlled by DTC-SVM. "حاليا، العديد من الأماكن تعاني من مشاكل في إمدادات المياه، مثل المواقع المعزولة في الصحراء. كما يعد نظام ضخ المياه بالطاقة الشمسية المستقل أحد الحلول المقترحة، والذي يحتاج إلى صيانة أقل مقارنة بأنظمة الطاقة الأخرى. حيث يتكون هذا النظام من مولد كهروضوئي، متصل بعاكس مصدر جهد مزود بمحرك حثي مقترن بمضخة ذات طرد مركزي. الهدف والغرض من هذه المذكرة هو استخدام تقنية التحكم المباشر في العزم (DTC) للتحكم في المحرك اللاتزامني الذي يستمد تغذيته عن طريق النظام الكهروضوئي، ولضمان التشغيل الأمثل للطاقة لهذا النظام عند ظروف مناخية مختلفة بمعية تقنية التحكم DTC مع تعديل طول النبضة الشعاعي (DTC-SVM) حيث يتم استخدام خوارزمية P&O لإنشاء المرجع المناسب. نقدم بين يديكم هذا المحتوى والذي ننناقش فيه النتائج المتحصل عليها لهذا النظام وهذا للتحقق من أداءه وجودته ، وكل ذلك تم باستعمال برنامج ماتلاب للمحاكات. "
Machine éléctrique مذكرة ماستر تخصص
Keywords: Induction Motor, Direct Torque Control, Voltage Source Inverter, Space Vector Modulation, Photovoltaic, Centrifugal Pump, Solar Energy, Maximum Power Point Tracking.; المحرك اللاتزامني، التحكم المباشر في العزم، مموج مصدر الجهد، تعديل الفضاء الشعاعي، الألواح الكهروضوئية، مضخة الطرد المركزي، الطاقة الشمسية ، (MPPT) تتبع النقطة القصوى للطاقة ، الطاقة المتجددة.